Time-of-flight Fourier Spectrometry with UCN. (September 2016) - Kulin, G.V.; Frank, A.I.; Goryunov, S.V.; Geltenbort, P.; Jentschel, M.; Bushuev, V.A.; Lauss, B.; Schmidt-Wellenburg, Ph.; Panzarella, A.; Fuchs, Y.
Abstract: The report presents the first experience of using a time-of-flight Fourier spectrometer of ultracold neutrons (UCN). The description of the spectrometer design and first results of its testing are presented. The results of the first experiments show that the spectrometer may be used for obtaining UCN energy spectra in the energy range of 60÷200 neV with a resolution of about 5 neV. The application of TOF Fourier spectrometry technique allowed us to obtain the energy spectra from the diffraction of monochromatic ultracold neutrons on a moving grating. Lines of 0, +1 and +2 diffraction orders were simultaneously recorded, which had previously been impossible to be done by other methods. These results have made it possible to make a comparison with the recent theoretical calculations based on the dynamical theory of neutron diffraction on a moving phase grating.